Big Data awareness and health care industry: An insight from Pakistan - Tanzeel Qaiser; Iram Fatima (Proceedings)
Introduction: Technologies like Big data are among one of the Quality 4.0 tools that seem to bring digital transformation in healthcare. Therefore, its awareness in healthcare providers is valuable to yield life-saving outcomes. A scarce literature has been found on the assessment of level of Big Data awareness, its utilization in healthcare and its role in firm performance.